Essential Oils Improve the Survival of Gnotobiotic Brine Shrimp (Artemia franciscana) Challenged With Vibrio campbellii - Zheng, Xiaoting; Han, Biao; Kumar, Vikash; Feyaerts, Adam F.; Van Dijck, Patrick; Bossier, Peter (Frontiers in Immunology, 2021)
The halophilic aquatic bacterium, Vibrio campbellii is an important aquatic pathogen, capable of causing vibriosis in shrimp and fish resulting in significant economic losses. In previous work, essential oils (EOs) extracts from Melaleuca alternifolia, Litsea citrata and Eucalyptus citriodora were found to inhibit the growth of V. campbellii in vitro. This study aimed to determine in vivo EOs’ potential protective effect towards gnotobiotic brine shrimp, Artemia franciscana, challenged with V. campbellii. The study showed that brine shrimp larvae supplemented with EOs of M. alternifolia (0.0008%) and L. citrata (0.002%) displayed significantly increased survival against V. campbellii. The results indicated that supplementation of these EOs increased the expression of immune-related genes (either in the presence or absence of the pathogen), probably contributing to enhanced protection. Furthermore, in vitro studies indicated that some EOs modulated the expression of virulence factors including swimming motility, biofilm formation and gelatinase and lipase activity, while flow cytometry data and regrowth assay indicated that these EOs do not exhibit antimicrobial activity as V. campbellii grew at the tested concentrations (M. alternifolia (0.0008%) and L. citrata (0.002%)). Our findings suggest that EOs extracted from M. alternifolia and L. citrata, can modulate virulence factor production and immunological responses and might hence become part of an intervention strategy to control vibriosis in a fish or shrimp aquaculture setting, a hypothesis that needs to be validated in the future.